Between Help and Hesitation:: How ELT Graduate Students Negotiate AI Use in Academic Practices - Agustin, Tari; Ashadi, Ashadi (International Journal of Language Teaching and Education, 2026)
Artificial Intelligence (AI) has become increasingly integrated into higher education, creating new opportunities for academic writing, research, and learning support. However, concerns regarding academic integrity, source reliability, and responsible AI use remain significant, particularly among future educators. This study explores how English Language Teaching (ELT) graduate students engage with AI tools in their academic practices. A qualitative approach was employed involving open-ended questionnaires completed by 13 ELT graduate students, followed by semi-structured interviews with five participants and reflective written responses from four participants. Data were analyzed using thematic analysis. The findings revealed three major themes: AI as Linguistic and Cognitive Scaffolding, negotiating trust, verification, and academic integrity, and emerging professional beliefs about responsible AI use. Participants perceived AI as a valuable resource for idea generation, academic writing, language development, and conceptual understanding. At the same time, they expressed concerns regarding fabricated references, misinformation, dependency, and originality, leading them to adopt verification practices such as source checking, cross-referencing academic materials, and revising AI-generated outputs. The findings further indicate that participants viewed AI not only as an academic tool but also as a pedagogical resource requiring critical and ethical use. Unlike studies that primarily focus on technology acceptance, this study highlights how future language educators actively negotiate the opportunities and challenges of AI through verification practices, ethical reflection, and professional responsibility. The study emphasizes the importance of integrating AI literacy, critical evaluation, and responsible technology use into teacher education programs to prepare educators for increasingly AI-mediated learning environments.